The Effects of Obesity and Physical Activity on Dyslipidemia in Persons With Type 2 Diabetes - Yun-A Shin; Jae-Hyun Kim; Ryuri Song; EunSeok Cha (Asian Society of Kinesiology, 2022)
OBJECTIVES This study was conducted to examine the effect of obesity, and physical activity on the prevalence of dyslipidemia in persons with type 2 diabetes mellitus (T2DM). METHODS A cross-sectional, correlational design was used. Participants aged 20 years or older were recruited from a diabetes clinic affiliated with a university hospital. Body composition, blood glucose, glycated hemoglobin, and blood lipid level were measured in addition to self-reported physical activity. Final data analysis was conducted with 177 participants. The differences on physical activity measures and body composition between those with or without dyslipidemia were analyzed using independent t-tests. The associations between dyslipidemia and physical activity and obesity were assessed with the odds Ratio (OR) and 95% confidence intervals (CI) after adjusting potential confounding factors. RESULTS The participation rate of regular physical activity in T2DM patients was 55.9%. BMI and regular physical activity participation influenced the prevalence of dyslipidemia in persons with T2DM. The regular physical activity participation rate of T2DM patients without dyslipidemia was higher than that of T2DM patients with dyslipidemia (p<.05). Moreover, participation in regular physical activity decreased the risk of dyslipidemia prevalence (p<.05). With regard to body composition, T2DM patients with dyslipidemia had a higher body mass index (p<.01). As the body mass index 1 increased, odd ratio of the dyslipidemia prevalence increased 1.21 times (p<.05). CONCLUSIONS The risk of dyslipidemia in T2DM patients was influenced by BMI and participation in regular physical activity. Therefore, reducing obesity through regular physical activity will be a way to lower the prevalence of dyslipidemia in T2DM.